Analisis Efektivitas Dan Efisiensi Pengelolaan Dana Desa Di Desa Sipodeceng Kecamatan Baranti Kabupaten Sidenreng Rappang - Rahmi, Rahmi; Salida , Amrizal; Taufiq, Muhammad (Paser Institute Of Accounting and Finance, 2025)
Background: Village Fund management plays a crucial role in promoting sustainable development and improving community welfare, thus requiring evaluation based on effectiveness and efficiency. Objective: This study aims to analyze the effectiveness and efficiency of Village Fund management in Sipodeceng Village, Baranti District, Sidenreng Rappang Regency, during the period 2021–2023. Method: The research employed a qualitative method with a narrative approach, using data collection techniques such as documentation of the village budget realization reports and interviews with the village head, secretary, and treasurer, analyzed through ratio calculations combined with narrative interpretation. Findings: The results indicate that the level of effectiveness is categorized as effective, with an average of 96% (>90%), reflecting the successful achievement of development targets, while efficiency averaged only 93%, below the 100% benchmark, suggesting relatively high resource utilization. Conclusion: Village Fund management in Sipodeceng Village is effective in achieving objectives but remains less efficient in budget utilization. The implications highlight the need for improved planning, transparency, and cost control to ensure that Village Funds are not only effective in achieving development goals but also efficient, accountable, and sustainable.